Implementasi Distributed Database Pada Learning Management System Menggunakan Platform Redhat Openshift - Bryant Plaudo Santoso; Agustinus Noertjahyana; Justinus Andjarwirawan (Jurnal Infra, 2020)
The use of technology now has begun to spread to the world of education. One of them is the use of E-Learning. In a learning management system, instructors can give assignments, materials, tests, or quizzes to students. But if many people access it, it can cause problems on the server. If the server goes down during an exam, it will be a serious problem because students will not be able to access the server. To overcome this, we need several web servers that are ready to serve users so that computing is not only focused on a web server. This research will test the implementation of distributed database on learning management system. The application will run on Openshift. Distributed databases will use MySQL Cluster by using sharding method that can make data into multiple partitions and stored on multiple database servers. With the implementation of distributed database, it is expected to increase the availability of applications. So when there is a database server down, the application can still be run properly. In addition, this can also minimize the database server to be overloaded because it is accessed by many users.